KAJIAN TENTANG IMPOR DAGING SAPI DI INDONESIA - Jiuhardi Jiuhardi (Faculty of Economics and Business Mulawarman University, 2015)
The aim of this study was to assess and determine the cause dependence Indonesia tehadap beef imported from abroad, especially Australia and the state mafia beef imports that occur from year to year as if Indonesia can not be separated from its dependency on imports. Currently, Indonesia has not been able to meet the needs of domestic beef. So it still would dependency of imported meat products. Dependence is caused by demand (demand) continues to increase, is inversely proportional to the availability (supply) of beef nationally. To meet the needs of society needed policies that support the implementation of food self-sufficiency needs, then comes the beef import policy from abroad, especially the cooperation with neighboring countries (Australia). One of the factors that cause Indonesia's dependence on imported beef is in demand (demand) of beef from the supply (supply). The increased demand caused by Indonesia's population continues to increase with the average of 2,404 hundred million, or in other words grew by 1.38 percent. In addition, the majority of Indonesia's population, or as many as 207 176 162 inhabitants (87.18 per cent) of whom are adherents of Islam and the largest in the World. Which is where most eating beef, especially at the time of religious celebrations, such as Eid al-Fitr and Eid al-Adha. Mafia beef imports is caused by: (1) Mental businessmen, bureaucrats and people who do not boast, (2) trade system persapian less efficient and effective as well as supervision of the less maksaimal and (3) The management system of import that have not been integrated between the with other parties. As for the hope of the future, among others: (1) Improving the mental businessmen, bureaucrats and society. (2) To encourage businesses to become cattle ranchers large scale in the form of PT, CV, SMEs, Firm and Cooperatives (3) Tightening oversight against the rules that apply for example, farmers may not sell cows that are still productive (regeneration) (4) Promotion of cattle farms in Indonesia in accordance with a tropical climate and land area in the hope of Indonesia may be the exporter of beef to other countries, (5) Mapping of cattle and the need for beef, (6) Implement integrated farming practices in order to achieve national self-sufficiency in meat..Â Keyword: Availability Beef, Mafia Import and Self-sufficiency National Meat